The workplace : - Pace, Joe (Joseph) (McGraw-Hill, 2006)
Book One is an orientation to the world of work. In it students consider the occupations that are most likely to have job openings in the coming years, how to prepare themselves to fill these openings, and what the workplace environment is like in the 21st-century. Professional business protocol, professional presence, and a customer-first attitude are also explored and discussed.